Updated View on the Relation of the Pineal Gland to Autism Spectrum Disorders - Shomrat, Tal; Nesher, Nir (Frontiers in Endocrinology, 2019)
Identification of the biological features of autism is essential for designing an efficient treatment and for prevention of the disorder. Though the subject of extensive research, the neurophysiological features of autism remain unclear. One of the proposed biological causes of autism is malfunction of the pineal gland and deficiency of its principal hormone, melatonin. The main function of melatonin is to link and synchronize the body’s homeostasis processes to the circadian and seasonal rhythms, and to regulate the sleep-wake cycle. Therefore, pineal dysfunction has been implicated based on the common observation of low melatonin levels and sleep disorders associated with autism. In this perspective, we would like to highlight several recent findings that support the hypothesis of pineal gland/melatonin involvement in autism. In addition, it has been suggested that abnormal neural plasticity such as cortical overgrowth and dendritic spine dysgenesis is a common neurological symptom in autism spectrum disorders. Here, we synthesize recent information and speculate on the possibility that abnormal metabolism of endogenous N,N-dimethyltryptamine (DMT), possibly from the pineal gland, might play a part in the development of autism. We hope that this manuscript will encourage future research of the DMT hypothesis and reexamination of several observations that were previously attributed to other factors, to see if they could be related to pineal gland/melatonin malfunction.